Development of Android Application-Based Volley Learning Media for Vocational High School Students - Ibrahim Ibrahim; Arjasman Sinaga; Ade Ros Riza; Usman Nasution (STAI Hubbulwathan Duri, 2023)
This study seeks to investigate how to develop learning materials for volleyball game material for class XI students. This study employed research and development (RD) techniques, including large group tests for 30 class XI students and small group tests for 15 class XI students. For this study, questionnaires and questions were handed out to experts and students to gather data. Both qualitative and quantitative data analysis techniques were utilised. The volleyball game material developed in class XI was validated by three experts - two media experts and one material expert. 43% of participants are familiar with needs analysis, whereas the average rating for validation falls within the unfavourable range of 29% to 46%. The small group test has a validity level of 59%, with the validation level suggesting that the average validation value falls between 47% and 64%, making it suitable for the large group testing phase. Validation tests for large groups typically yield results ranging from 83% to 100%, indicating successful development of learning media for volleyball game material in class XI, falling within the very good category, and proving to be efficient and effective. In a recent test, 65% of students in the small group of 15 scored in the